Metabotropic glutamate receptors (mGluRs) in epileptogenesis: an update on abnormal mGluRs signaling and its therapeutic implications - Leyi Huang; Wenjie Xiao; Yan Wang; Juan Li; Jiaoe Gong; Ewen Tu; Lili Long; Bo Xiao; Xiaoxin Yan; Lily Wan (Neural Regeneration Research, 2024)
Epilepsy is a neurological disorder characterized by high morbidity, high recurrence, and drug resistance. Enhanced signaling through the excitatory neurotransmitter glutamate is intricately associated with epilepsy. Metabotropic glutamate receptors (mGluRs) are G protein-coupled receptors activated by glutamate and are key regulators of neuronal and synaptic plasticity. Dysregulated mGluR signaling has been associated with various neurological disorders, and numerous studies have shown a close relationship between mGluRs expression/activity and the development of epilepsy. In this review, we first introduce the three groups of mGluRs and their associated signaling pathways. Then, we detail how these receptors influence epilepsy by describing the signaling cascades triggered by their activation and their neuroprotective or detrimental roles in epileptogenesis. In addition, strategies for pharmacological manipulation of these receptors during the treatment of epilepsy in experimental studies is also summarized. We hope that this review will provide a foundation for future studies on the development of mGluR-targeted antiepileptic drugs.